QUR’ANIC LITERACY COMPETENCE OF ELEMENTARY TEACHERS: THE ROLE OF RELIGIOUS HABITUS AND SOCIAL CAPITAL - Akhsanul Fuadi; Aida Hayani; Ahmad Salim; Hilalludin Hilalludin; Shada Al-Nomani (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the role of religious habitus and social capital in shaping Qur’anic literacy competence among Islamic Religious Education (PAI) teachers at the elementary school level in the Special Region of Yogyakarta. A qualitative multiple case study design was employed to capture in-depth and contextualized insights from several selected schools. Data were collected through in-depth interviews, classroom observations, and document analysis involving PAI teachers, school leaders, and supporting informants. Data analysis followed an interactive model, including data reduction, data display, and verification, with interpretation guided by a sociological framework. The findings reveal that Qur’anic literacy competence is not merely a technical skill but a socially constructed capacity shaped by the interaction between internalized religious dispositions and external relational networks. Teachers with strong religious habitus demonstrate higher fluency, confidence, and interpretative teaching practices, while social capital enhances competence through continuous learning and collaborative engagement. Variations in competence are closely linked to differences in formative experiences and access to supportive networks. The study contributes theoretically by integrating sociological perspectives into Islamic education, particularly in understanding teacher competence as a dynamic and relational process. Practical implications highlight the importance of strengthening religious habitus and expanding social capital through institutional support and professional learning communities. These findings suggest that sustainable improvement in Qur’anic literacy competence requires a holistic approach that aligns individual, social, and institutional dimensions.